Guyana initial national communication in response to its commitments to the UNFCCC ([s.n.] [S.l.], 2002)
Looks at the national circumstances in 1994 and reports on the national inventory of greenhouse gases. Focuses on Guyana's vulnerability to climate change and impacts such as sea level rise, especially in the coastal zone, and in water resources, agriculture, forestry, energy and health sectors. Examines adaptation measures and notes that these will require substantial financial and technical assistance. Highlights mitigation measures that will have to be employed and technology transfer that will be necessary. Stresses the need for systematic observation and research. Notes that education, public awareness and training will be essential tools for avoiding future chaos.
Bibliography : p. 170-175